Evaluation of a testing device for comparing unbalance characteristics of table tennis balls - Kornfeind, P.; Baca, A.; Gastinger, R. (Procedia Engineering, 2012)
A method for quantifying unbalance characteristics of table tennis balls has been developed. The method has been validated and tested threefold: 1. Subjective ranking of balls by professional players, 2. high speed video recordings of spinning balls, motion reconstruction, and ranking according to the oscillation amplitudes observed and 3. investigation of the sensitivity of the method by slightly changing the balance characteristics of one ball artificially. The results from the rankings were compared to the ranking obtained from applying the proposed method. In addition, simulation studies for the testing device have been performed. Good agreement between methods was observed.